Experiencing food insecurity in childhood: influences on eating habits and body weight in young adulthood - Lise Dubois; Brigitte Bédard; Danick Goulet; Denis Prud'homme; Richard E Tremblay; Michel Boivin (Cambridge University Press, 2023)
Abstract Objective: To examine how food insecurity in childhood up to adolescence relates to eating habits and weight status in young adulthood. Design: A longitudinal study design was used to derive trajectories of household food insecurity from age 4·5 to 13 years. Multivariable linear and logistical regression analyses were performed to model associations between being at high risk of food insecurity from age 4·5 to 13 years and both dietary and weight outcomes at age 22 years. Setting: A birth cohort study conducted in the Province of Quebec, Canada. Participants: In total, 698 young adults participating in the Québec Longitudinal Study of Child Development. Results: After adjusting for sex, maternal education and immigrant status, household income and type of family, being at high risk (compared with low risk) of food insecurity in childhood up to adolescence was associated with consuming higher quantities of sugar-sweetened beverages (ß adj: 0·64; 95 % CI (0·27, 1·00)), non-whole-grain cereal products (ß adj: 0·32; 95 % CI (0·07, 0·56)) and processed meat (ß adj: 0·14; 95 % CI (0·02, 0·25)), with skipping breakfast (ORadj: 1·97; 95 % CI (1·08, 3·53)), with eating meals prepared out of home (ORadj: 3·38; 95 % CI (1·52, 9·02)), with experiencing food insecurity (ORadj: 3·03; 95 % CI (1·91, 4·76)) and with being obese (ORadj: 2·01; 95 % CI (1·12, 3·64)), once reaching young adulthood. Conclusion: Growing up in families experiencing food insecurity may negatively influence eating habits and weight status later in life. Our findings reinforce the importance of public health policies and programmes tackling poverty and food insecurity, particularly for families with young children.